Optimizing hybrid vigor: a comprehensive analysis of genetic distance and heterosis in eggplant landraces - Rajan, Neha; Debnath, Sandip; Perveen, Kahkashan; Khan, Faheema; Pandey, Brijesh; Srivastava, Akanksha; Khanam, Mehrun Nisha; Subramaniyan, Vetriselvan; Kumarasamy, Vinoth; Paul, Pronob J.; Lal, Mohan (Frontiers in Plant Science, 2023)
This study delves into the molecular characterization of 14 genotypes of eggplant (brinjal) to assess their genetic diversity and the effect of heterosis. The genetic diversity analysis revealed polymorphisms in eight out of twenty SSR markers across the parental lines. A high genetic distance was found between some parents, and parental lines were grouped into five clusters based on the Unweighted Pair Group Method of Arithmetic Means (UPGMA). This diversity suggests a broad genetic base and informs potential future hybridization programs. Examining yield and yield-related traits among parents and hybrids demonstrated significant heterosis over mid, superior, and standard parents, particularly in fruit yield per plant. The crosses RKML-26 X PPC and RKML1 X PPC exhibited notable heterosis over mid and better parents, respectively, with significant heterotic effect for yield and marketable yield per plant. Interestingly, the study found that genetic distance and heterosis were positively correlated only up to a certain threshold. Moderate genetic distance between parents often resulted in hybrids with higher heterosis than those from parents with a very high genetic distance. The study contributes to our understanding of the relationship between genetic distance and heterosis, highlighting the importance of appropriate parent selection in hybrid breeding programs. Future research should further investigate the genetic mechanisms driving heterosis and the impact of varying genetic distances on the heterotic effect. These findings hold significant potential for enhancing crop yield and economic value through strategic breeding programs.